Assessment of Cluster Front Line Demonstrations on the Yield and Economics of Mustard under National Food Security Mission in Bharatpur District of Rajasthan, India - Meena, K. A.; Gupta, J. K.; Meena, R. L. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during rabi season (October–March) from 2016–17 to 2021–22 (6 consecutive years) in different villages of the Bharatpur district of Rajasthan to assess the performance of cluster front line demonstrations on mustard through improved varieties, seed rate, seed treatment, application of sulphur, disease and pest management on production and productivity. Krishi Vigan Kendra, Kumher, Bharatpur (Sri Karan Narendra Agriculture University, Jobner, Jaipur), Rajasthan conducted 800 front line demonstrations in an area of 320 ha on mustard crop variety DRMRIJ-31 (Giriraj) during 2016–17, 2017–18, 2018–19, 2019–20, 2020–21 and 2021–22. The results of study exhibited that the average yield under demonstrated plots ranged from 13.42 to 26.19 q ha-1 with a mean of 20.98 q ha-1, which was 18.26% more yield as compared to farmer’s practices (17.74 q ha-1). The study showed mean extension gap of 323.83 kg ha-1, mean technology gap of 602.33 kg ha-1 with mean technology index of 22.31%. Higher mean net return of ` 65064 ha-1 with mean benefit: cost ratio of 3.57 was found with improved technologies in comparison to farmer’s practices (` 53760 ha-1). Consequently, the results revealed that the adoption of improved technologies with scientific participation contributed to enhance the production and productivity of mustard in Bharatpur district.